Investigation into Radiation Doses to Patient During Diagnostic Imaging - Khalid, Dastan (Sulaimani Journal for Pure and Applied Sciences, 2013)
Investigation in doses delivered to patient during an X-ray imaging is carried out. From the data obtained, the Entrance Surface Dose (ESD) is calculated and compared to the Reference Dose Levels of other countries (UK, Australia and the US). The results show 93% of chest examination was cases of overdose, while some other examinations had 8.5% overdose by more than 3 times. The results suggests that during X-ray imaging patients receive doses more than the reference level at the Sulaimani Hospital.
Keywords: Radiation Dose; Dose Reference Level; Entrance Dose,Dose during diagnostic imaging